Terrorism and Violence: a Danger to the Development of Nationhood - Aslam, Mohd Mizan Mohammad; Shuib, Shushil Azam; Mizan, Muhd Nabhan (Indo Consultan Energi, 2024)
The objective of this paper is to discuss how violence and terrorism become a threat to nation-buildings. The main aspects of discussions are collective security, securitization, national security and human security. These four aspects play major roles to build nationhood. If one of these elements is threaten, it will jeopardize the nationhood buildings. Thus, it is important to identify these key factors to stabilize nationhood. This paper will also relate the relationship between human safety and national security where national security can be threatened if the people are insecure. This paper focused on Malaysian Nation-Building with the rise of extremism in this region between the year of 2000-2016. Secondary data collections are through literature review and observation from various sources. Findings has been translated into this paper with the main factor on threat of building nationhood by violence and terrorism.